International political analysis - Edwards, David V. (New York, 1970)
If international relations in the late twentieth century are tempestuous, the academic discipline that studies them is, in its own way, equally unettled. There has never been general agreement among scholars about the most fruit ful approach to the study of international politics, nor have scholars agreed on the substance of the knowledge we have about why those relations take the forms they do. In general, academic thought about international relations has tended to be oversimplified: not too long ago, it was widely believed that the study of world order and the institutions that might characterize it was the most promising, but then, this "Idealist approach was challenged by a position that might without great inaccuracy be termed its opposite the self-styled "Realist" view that nations may be assumed to act in selfish, power-oriented ways in all instances, and that if they do not, they should be criticized for fail ing. In the 1960's, however, both the residual Idealism and its assassin, Real ism, have been increasingly replaced by a loose collection of approaches de veloped in the social sciences. These approaches are characterized primarily by the rejection of simple assumptions about the motives of nations, and ex ploration of the possibilities of applying new insights and procedures developed in the social sciences to the study of the conduct of nations.
Keywords: International Relations